Climate Justice - Bartmann, Marius; Halsband, Aurélie; Schapper, Andrea (2023)
Human activities associated with greenhouse gas emissions have unequivocally caused global warming. Widespread adverse impacts on people, living organisms, and the environment are already being observed, mostly affecting vulnerable communities who are least responsible for current climate change. Unless drastic mitigation and adaptation measures are taken, continued greenhouse gas emissions will further exacerbate dangerous climate change. This expert report maps and analyses the complex justice issues that arise in the context of climate change and evaluates policy responses to the impacts of climate change from a climate justice perspective.